2022
DOI: 10.1111/aos.15164
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal and neonatal factors and morphology of the optic nerve head in the Northern Finland birth cohort

Abstract: Purpose The optic nerve head (ONH) is a part of the brain that can be evaluated through the transparent medium of the eye. The purpose of this study was to explore the possible correlations among the properties of the optic nerve head, maternal factors during pregnancy and neonatal parameters in a randomized sample of a birth cohort. Methods The Northern Finland 1966 Birth Cohort has been prospectively monitored since their antenatal period. Data on pregnancy and neonatal period were collected during gestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The Northern Finland birth cohort demonstrated that subjects whose mothers had chronic pulmonary disease during pregnancy showed a statistically significant smaller optic nerve head at the age of 46–48 years, indicating the effects of intrauterine hypoxia on optic nerve development 45 . Moreover, maternal smoking during pregnancy was independently associated with a thinner retinal nerve fiber layer at age 11 or 12 years 46 .…”
Section: The Eye and Developmental Origins Of Health And Diseasementioning
confidence: 99%
“…The Northern Finland birth cohort demonstrated that subjects whose mothers had chronic pulmonary disease during pregnancy showed a statistically significant smaller optic nerve head at the age of 46–48 years, indicating the effects of intrauterine hypoxia on optic nerve development 45 . Moreover, maternal smoking during pregnancy was independently associated with a thinner retinal nerve fiber layer at age 11 or 12 years 46 .…”
Section: The Eye and Developmental Origins Of Health And Diseasementioning
confidence: 99%